Angular Distribution of electron temperature and density in a laser-ablation plume - LUNNEY, JAMES GERARD (American Physical Society, 2000)
The angular distribution of electron temperature and density in a laser-ablation plume has been studied for the first time. The electron temperature ranges from 0.1 to 0.5 eV and is only weakly dependent on the angle in the low-intensity range studied here. In contrast, the typical ion energy is about 2 orders of magnitude larger, and its angular distribution is more peaked about the target normal. The derived values of the electron density are in agreement with the measured values of ion density.
PUBLISHED
Keywords: Physics